2019
DOI: 10.1016/j.jagp.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between C-Reactive Protein and Postoperative Delirium Differs by Catechol-O-Methyltransferase Genotype

Abstract: Objectives: Catechol-O-methyltransferase (COMT), a key enzyme in degrading stress hormones, may influence susceptibility to delirium. Individuals with the COMT (rs4680) Val/Val genotype (designated “warriors”) withstand the onset of neuropsychiatric disorders and cognitive decline, while individuals with Met/Met and Val/Met genotypes (“non-warriors”) are more susceptible to these conditions. We evaluated whether COMT genotype modifies the established association between acute phase reactant (stress marker) C-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…These findings (e.g., Ref. ) support the notion that delirium pathophysiology is complex and warrants examination beyond direct gene association studies. Separately, work in AD pathophysiology has uncovered complex biological mechanisms of AD by the identification of gene and protein networks contributing to an AD‐specific immune‐endocrine‐neuronal regulatory network .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These findings (e.g., Ref. ) support the notion that delirium pathophysiology is complex and warrants examination beyond direct gene association studies. Separately, work in AD pathophysiology has uncovered complex biological mechanisms of AD by the identification of gene and protein networks contributing to an AD‐specific immune‐endocrine‐neuronal regulatory network .…”
Section: Discussionsupporting
confidence: 66%
“…Evidence for other indirect genetic influences has been observed in previous examinations of gene‐protein interactions with postoperative delirium. For instance, although no direct association between catechol‐O‐methyltransferase (COMT) genotype, a key regulator of the stress response, and postoperative delirium was observed, COMT genotype was found to modify the previously reported association between inflammatory marker C‐reactive protein (CRP) and postoperative delirium . Among older surgical patients with the COMT Val/Val genotype, high CRP measured on postoperative day 2 (POD2) was not associated with delirium.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Perturbations in executive function can result in delirium which affects mainly attention, and dementia which affects mainly memory. Although COMT does not appear to directly influence delirium, it modified the known association between C-reactive protein (CRP), an acute phase reactant, and postoperative delirium [34,35] Functional pain disorders A recent meta-analyses of COMT and functional pain disorders found that the low-activity met-allele was associated with fibromyalgia. An earlier meta-analysis also found that the met-allele was associated with fibromyalgia and widespread chronic pain, but not migraine headache or chronic musculoskeletal pain conditions [36,37] Chronic fatigue syndrome Chronic fatigue syndrome patients were more likely to be homozygous for the met-allele compared with val-allele carriers [38,39] Pain COMT low-activity haplotypes were associated with greater sensitivity to nociceptive, but lower sensitivity to neuropathic pain.…”
Section: Deliriummentioning
confidence: 99%
“…These include direct and indirect effects of inflammatory, neuroendocrine, and gross anatomic or neurodegenerative mechanisms [ 7 ]. Moreover, candidate gene association studies on delirium have shown that apolipoprotein E [ 8 ], catechol-O-methyltransferase (COMT) [ 9 ], and dopamine-signaling genes such as dopamine receptor 2 [ 10 ] are related to the risk of delirium. Interleukin-related genes and the sodium/hydrogen exchanger gene were also identified as risk factors for delirium by a delirium-focused genome-wide association study (GWAS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%